2013
DOI: 10.4103/0971-5851.116185
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical profile of triple negative breast cancer at a cancer hospital in North India

Abstract: Background:Triple negative breast cancer (TNBC) is a recent concept and the burning topic of research today. Various studies have been reported in western literature on TNBCs or the similar group of basal like cancers, all highlighting the poor prognostic features of this molecular subtype in comparison to the other types of breast cancers. However extensive data from India is lacking. The aim of this study was to analyze the epidemiological and clinical profile of TNBcs at our institute.Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
18
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 9 publications
18
18
4
Order By: Relevance
“…In contrast to this, other studies showed different frequencies of triple negativity as 25% (Ambroise et al, 2011) and 11.8% (Sharma et al, 2013) in Indian data. The median age at diagnosis was 49 years which showed similarity to (Thike et al, 2010;Rao et al, 2013) and variation from other studies (Dent et al, 2007;Suresh et al, 2013). Clinically stage II was the commonest stage at presentation in accordance to the previous findings (Niwińska et al, 2010;Rao et al, 2013;Suresh et al, 2013) followed by III and I.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to this, other studies showed different frequencies of triple negativity as 25% (Ambroise et al, 2011) and 11.8% (Sharma et al, 2013) in Indian data. The median age at diagnosis was 49 years which showed similarity to (Thike et al, 2010;Rao et al, 2013) and variation from other studies (Dent et al, 2007;Suresh et al, 2013). Clinically stage II was the commonest stage at presentation in accordance to the previous findings (Niwińska et al, 2010;Rao et al, 2013;Suresh et al, 2013) followed by III and I.…”
Section: Discussionsupporting
confidence: 88%
“…One of the study from Maharashtra found 71.35% women presenting in late stage at the time of diagnosis of breast cancer (Mohite et al, 2015). Similar observations were noted by studies from north and south Indian populations also (Suresh et al, 2013;Kokiwar, 2011;Hiremath et al, 2012;Agrawal, 2012). Badwe et al (2011) observed maximum cases with grade III tumor (75.4%) and invasive breast cancer(95.4%).…”
Section: Clinicopathological Profile Of Breast Cancer Patients At a Tsupporting
confidence: 87%
“…[ 6 ] have reported that in the US the prevalence of TNBC breast cancer among patients with all forms of breast cancer was 12.4% and that this prevalence was highest among nonHispanic black patients with breast cancer, at 24.6%. In India, the incidence of TNBC was varies from 12.5% to 29.8%[ 7 8 9 ]…”
Section: Discussionmentioning
confidence: 99%